Examining the relationship between SME size and corporate DEI-related activities - Tikkanen, Jenna (My University, 2024)
The purpose of this study is to explore the current state of small and medium-sized enterprises’ social sustainability within the EU context. More specifically, this study aims to identify if there is a relationship between firm size and the depth of adopted diversity (differences between groups of individuals), equity (an individual’s access to needed benefits), and inclusion (perceived sense of belonging) related actions in small and medium-sized enterprises. Currently the EU is seeking sustainable development through various sustainability initiatives, which inflict significant changes to the corporate sustainability within the European economic market. One of these initiatives, the Corporate Sustainability Reporting Directive, has extensive impacts on the European companies of all sizes. Despite not directly complying with the directive, small and medium-sized enterprises are forced to practice sustainability reporting within their value chains. As these companies have not been mandated to report previously, the Corporate Sustainability Reporting Directive may impose greater preparation efforts for companies without prior sustainability reporting experience. Theoretically this study builds on literature regarding mandatory and voluntary sustainability reporting, its potential impacts on small and medium-sized enterprises, and the current state of social sustainability in these companies. This is a quantitative study that utilizes data collected from a survey conducted by the Erasmus+, EU-co-funded DEI4SME project. Ordinal logistic regression has been selected as the analysis methodology. The results do not reveal statistically significant relationships between firm size and diversity, equity, and inclusion related actions. However, the non-significant findings indicate an inverse relationship between firm size and the adoption of diversity, equity, and inclusion related actions such that survey respondents have rated micro and small companies’ actions higher than medium-sized companies’.
Keywords: small and medium-sized enterprises; sustainable development; social sustainability; diversity; inclusion; sustainability reporting; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development